Cofnodion - Hunangofiant Meic Stephens - Stephens, Meic (Y Lolfa, 2012)
Meic Stephens' autobiography - the experienced author, professor, journalist, translator, poet and editor gives an account of how the young boy from an English-speaking household grew up to be a Welshman, and played a prominant part in welsh culture. Intro – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Diolchiadau – Lluniau.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books